Injuries of the biceps and superior labral complex in overhead athletes - Morse, K. W.; Eno, J.-J.; Altchek, D. W.; Dines, J. S. (Current Reviews in Musculoskeletal Medicine, 2019)
Purpose of Review: To summarize the current anatomy, biomechanics, presentation, treatment, and outcomes of injuries to the biceps and superior labral complex in overhead athletes. Recent Findings: The biceps and superior labral complex is composed of anatomically distinct zones. The inability to accurately diagnose biceps lesions contributes to continued morbidity especially as arthroscopy and advanced imaging fail to fully evaluate the entire course of the biceps tendon. Superior labrum anterior and posterior (SLAP) repair, long head of biceps tenodesis, and tenotomy are the most common operative techniques for surgical treatment of biceps-labral complex (BLC) pathology. Labral repair in overhead athletes has resulted in mixed outcomes for athletes and is best indicated for patients under age 40 years old. Summary: Injuries to the BLC are potentially challenging injuries to diagnose and treat, particularly in the overhead athlete. SLAP repair remains the treatment of choice for high-level overhead athletes and patients younger than 40 years of age, while biceps tenodesis and tenotomy are preferred for older patients.